Fear of the angry mob. Issue 2 (4th May 2021) - Jasper, James M.
ABSTRACT: The Capitol breach that occurred on 6 January 2021 immediately revived images of protest crowds as irrational, emotional, violent, and out of control. This frame had flourished for millennia, but had been displaced by more sympathetic ideas about protest in recent decades. Inspired by the civil rights and feminist movements, scholars had come to see street protest as politics by extraordinary means for those closed off from more mainstream channels of influence. Journalists, politicians, and police did not entirely change their minds along with researchers, but they had softened their views somewhat: protestors are not necessarily criminals to be attacked. In a society where protest is common, Americans had developed more nuanced thinking and feelings about crowds – all of which went out the window on January 6th. In this paper I trace some of the history of European and American ideas about crowds in order to show how easy – and how mistaken – it is to see a crowd of protestors as "a hostile crowd" or "a violent crowd, " or simply "the mob."